International Encyclopedia of Civil Society - Anheier, Helmut K.; Toepler, Stefan; SpringerLink (Online service) (New York, NY : Springer US, 2010)
Renewed and growing interest in the topic of civil society has generated a wealth of new information and knowledge on the subject, but until now, there was no comprehensive reference work to organize and consolidate this knowledge. The International Encyclopedia of Civil Society will fill this gap, creating a framework for cross-disciplinary communication by providing succinct summaries of concepts and theories, definitions of terms, biographical entries, and organizational profiles. It will also serve as a guide to sources of information, and an overview of the contours of civil society, social capital, philanthropy and nonprofits in different parts of the world, and across cultures and historical periods. The key purpose of the encyclopedia is to provide a common set of understandings and a terminological and analytical starting point for the future development in the growing field of civil society studies worldwide. At the international level, the encyclopedia will represent the most systematic intellectual stocktaking of a growing and rapidly developing field. The International Encyclopedia of Civil Society will have considerable appeal to researchers in nonprofit and civil society studies, political science, economics, management studies, social enterprise as well as development studies programs.
Intro -- Foreword -- Acknowledgments -- Encyclopedia Entries -- Conclusion -- Appendix -- Index.
Keywords: SOCIAL SCIENCES; ECONOMIC POLICY; ECONOMICS; SOCIAL SCIENCES; SOCIOLOGY, GENERAL; POLITICAL SCIENCE, GENERAL; BUSINESS/MANAGEMENT SCIENCE, GENERAL; PUBLIC HEALTH/GESUNDHEITSWESEN.; ECONOMIC POLICY